2020
DOI: 10.21769/bioprotoc.3605
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Bacteria Residing in Caenorhabditis elegans Intestine

Abstract: Quantification of intestinal colonization by pathogenic or commensal bacteria constitute a critical part of the analysis to understand host-microbe interactions during different time points of their interplay. Here we detail a method to isolate non-pathogenic and pathogenic bacteria from C. elegans intestines, and classify gut phenotypes induced by bacterial pathogens using fluorescently-tagged bacteria. Furthermore, these methods can be used to isolate and identify new culturable bacterial species from natura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
(2 reference statements)
0
10
0
Order By: Relevance
“…S4, E to G). To investigate whether there are differences in the accumulation of E. coli HB101 and P. aeruginosa PAO1 in the intestines of wild-type and mutant worms, we performed colony-forming unit (CFU) assays ( 49 , 50 ). We observed that tent-5 –deficient worms had higher bacterial load in their guts compared to the wild type ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S4, E to G). To investigate whether there are differences in the accumulation of E. coli HB101 and P. aeruginosa PAO1 in the intestines of wild-type and mutant worms, we performed colony-forming unit (CFU) assays ( 49 , 50 ). We observed that tent-5 –deficient worms had higher bacterial load in their guts compared to the wild type ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Exposure of wild-type and mutant worms to E. coli HB101 and P. aeruginosa PAO1 was carried out exactly as for life-span and killing assays described above. CFU assays were performed essentially as described in ( 49 , 50 ) with minor modifications. Briefly, on the 5th (HB101) and 4th (PAO1) day of adulthood, 30 worms of each genotype from each of the three technical replicate plates were collected into 50 μl of 1× M9 supplemented with 25 mM levamisole (Sigma-Aldrich, L9756) to inhibit pharyngeal pumping and expulsion.…”
Section: Methodsmentioning
confidence: 99%
“…Such observations may be more likely to come from natural rather than artificial experimental situations and so represent real circumstances, but each observation still represent one animal captured at one point in time and space, which may, or may not, be representative of the conditions occurring most frequently. Examples include several different methods of observation but most frequently on predators, with fewer microbial feeders and parasites of plants: diatom pigments detected in the gut of microbial feeders by HPLC (Majdi et al 2012); direct microscopic observations of bacteria in the gut of a different sort of microbial feeder (Arpin & Kilbertus 1981); observations of fluorescent tagged bacteria in the gut of another type of microbial feeder (Palominos & Calixto 2020); nitrogen isotope ratios and fatty acid composition of different microbial feeders (ruess et al. 2004), and studies using radioactive labelling, PCr of gut contents or direct observations of distinctive parts of various prey in the guts of predators (Cabos et al 2013, Fonseca & Galluci 2008, Jensen 1992, Lopez et al 1979, Mohilal & Dhanachand 1992, Small 1987, Wang et al 2015.…”
mentioning
confidence: 99%
“…In the established methodology the 48-h infected C. elegans were submitted to the described double filtration, first using 41-µm pore size filter to discard bacterial clusters, and then using a 10-µm pore size filter to retain the nematodes and separate them from free bacteria. When collected, C. elegans were, on average, infected with 6 × 10 3 CFUs/worm, a value in accordance with literature (Palominos and Calixto 2020). About 300,000 nematodes were used per replicate, to obtain a total of ~ 10 9 CFUs per sample.…”
Section: Development Of a Model For Bacterial Transcriptional Analysi...mentioning
confidence: 76%